P5 Activity Management Based on the Local Wisdom of the Banyumasan Community in Kindergarten - Mukti Amini; Novan Ardy Wiyani; Ernayanti Nur Widhi; Murni Murni (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Despite the increasing implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) in Indonesian early childhood education, many teachers continue to struggle to design culturally meaningful project-based learning activities that effectively integrate local wisdom into the curriculum. This study addresses this gap by developing and validating a management model for P5 activities grounded in the local wisdom of the Banyumasan community. Employing a collaborative action research design with an applied research approach, the study was conducted at Tunas Bangsa Adireja Kulon Kindergarten in Central Java, Indonesia, involving one principal, three teachers, and 39 children. Data were collected through semi-structured interviews, participant observations, and document analysis, and analyzed using an interactive model of data reduction, data display, and conclusion verification. The findings reveal a three-stage management framework for implementing P5 activities grounded in local wisdom. The first stage, local wisdom planning, involves designing project modules that integrate Banyumasan cultural values, traditions, and local products into learning objectives and classroom activities. The second stage, local wisdom action, engages children in experiential learning through the exploration, production, and practice of culturally authentic local wisdom artifacts under teacher facilitation. The third stage, reflective local wisdom assessment, employs structured reflection and recall activities to evaluate children's learning experiences while reinforcing cultural identity and value internalization. The study contributes a transferable framework for managing culturally responsive project-based learning in early childhood education that may be adapted to diverse cultural contexts. By demonstrating how indigenous knowledge can be systematically integrated into project management, this research provides practical guidance for teachers and policymakers seeking to strengthen culturally sustainable education, foster children's character development, and preserve local cultural heritage.